Lung function evaluation in heart failure: possible pitfalls. Issue 1 (March 2020) - Contini, Mauro; Conte, Edoardo; Agostoni, Piergiuseppe
A 59-year-old male former smoker, with a history of hypertension, diabetes and chronic ischaemic heart disease (prior non-ST-elevation myocardial infarction and percutaneous coronary intervention+stent on circumflex and descending anterior coronary arteries) was referred to our lab for progressive dyspnoea of unknown origin. Even if a temporary moderate left ventricular systolic dysfunction had been observed during the acute phase of non-ST-elevation myocardial infarction, a cardiac ultrasound performed a few months after revascularisation showed a normal systolic function. At the time of the visit, the patient complained of a progressive functional capacity decline in the last 3 months, with shortness of breath after more than usual efforts (New York Heart Association class II). Pharmacological treatment included amlodipine, ivabradine, low dose diuretics, acetylsalicylic acid and metformin. At physical examination rhythmic pulse (70 bpm) and normal arterial pressure (120/70 mmHg) were detected, together with minimal dependent oedema, absence of jugular distention, bibasilar reduced breath sounds with rare fine crackles and soft cardiac tones with grade 2 holosystolic murmur. Resting ECG was normal, except for signs of a previous inferior myocardial infarction. Resting pulmonary function test (PFT) showed a severe restrictive deficit with moderate reduction in lung diffusion for carbon monoxide ( D LCO ) entirely due to a reduction in the alveolar volume ( V A ). A maximal cardiopulmonary exercise test (CPET) showed a severe reduction in exercise capacity with ventilatory limitation to exercise and a restrictive ventilatory pattern. However, further investigations led to diagnosis of heart failure. Indeed, a chest radiograph (figure 1) showed vascular congestion and pleural effusion, cardiac ultrasound showed a severe reduction in left ventricular systolic function (23.5%) with left ventricular dilation, increased left ventricular filling pressure and pulmonary hypertension and brain natriuretic peptide (BNP) was significantly altered (579 pg·mL −1 ). A primary lung disease was excluded by computed tomography lung scan. Close to acute heart failure, a restrictive and/or obstructive lung impairment can be detected in the absence of any primitive lung disease. To avoid diagnostic pitfalls, lung function evaluation should be delayed until after full patient recovery. http://bit.ly/3aEy8ed